PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PT. PERKAPALAN DI PROVINSI SULAWESI TENGGARA - , Laode Peli, SKM, Prof. Dr. dr. Adi Heru Sutomo, M.Sc.,D.Comm.Nutr.DLSHTM.PKK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the application of Occupational Health and Safety Management System in the shipping company in Southeast Sulawesi. Research conducted the study at PT. Indonesian Ferry Bajoe - Kolaka to know the Occupational Health and safety policies, facilities and infrastructure in the implementation, quality and quantity of employees, ship maintenance procedures and emergency response procedures in the ship. This research is qualitative using interview and observation of human resource department, document control, ship crew, port health office and the portâs quarantine office. The results showed that the company has owned environmental Health and safety division but is still joined with document control division. Safety and health management, education / training of employees and audit have been implemented by the company. Facilities and infrastructure have been owned by the company, but some of the equipments still need to be completed namely organic dumpster, inorganic dumpster and hazardous and toxic substances dumpster, evacuation routes and safe assembly point outside the building, as well as some safety equipment on board. Ship maintenance is conducted on the daily maintenance / routine, periodic, critical care and docking with the company's internal procedures. For handling emergencies on board, the company has owned internal procedures involving various branches and divisions in the company at the center as well as the emergency handling on board.